After the revolution : essays in memory of Anjan Ghosh - Chatterjee, Partha(ed.) (New Delhi Orient Blackswan Private Ltd, 2020)
Anjan Ghosh (1951 2010), an exemplary Marxist sociologist and teacher, belonged to the generation of intellectuals that dreamt of a socialist India, and saw both the rise and demise of the Communist Party in West Bengal. He died a year before Trinamool Congress dislodged the Left from power. But long before his death, the fall of the Soviet Union had initiated a re-evaluation among Marxists in West Bengal and elsewhere of the twentieth-century history of socialism. The present crisis of liberal capitalism, however, compels a fresh, critical look at the legacy of the Russian Revolution today. After the Revolution is a tribute by Anjan Ghosh s friends and colleagues not only to his memory, but also to the idea of revolution, through a cosmopolitan quest for a liveable alternative to capitalism. It reflects on the Russian Revolution, as viewed from our current location, and re-examines some of the basic tenets of revolutionary theory and practice in the twentieth century, to shed light on the present. Exploring the limits of capitalism, liberal democracy and socialism, the essays examine a range of issues, including contemporary political movements, Maoism and Indian democracy, the later Marx s thoughts on Russia, global finance dynamics, and the impact of a revolution aesthetic on literature, music and cinema. Original, eclectic, insightful, these timely essays are addressed to students and scholars of sociology, history and culture studies.
Contributed articles.
Includes bibliographical references.
Keywords: Socialism; Democracy; Revolutions; Revolutions; Democracy; Revolutions; Socialism